2017
DOI: 10.1155/2017/7262464
|View full text |Cite
|
Sign up to set email alerts
|

Use of Red Cactus Pear (Opuntia ficus-indica) Encapsulated Powder to Pigment Extruded Cereal

Abstract: Encapsulated powder of the red cactus pear is a potential natural dye for the food industry and a known antioxidant. Although the use of this powder is possible, it is not clear how it alters food properties, thus ensuing commercial acceptability. The aim of this study was to evaluate the effect of encapsulated powder of the red cactus pear on the physicochemical properties of extruded cereals. The powder was mixed (2.5, 5.0, and 7.5% w/w) with maize grits and extruded (mix moisture 22%, temperature 100 ∘ C, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The water absorption index (WAI) was determined according to the method described by Ruiz-Gutiérrez et al [24]. The extruded shell or the control (non-extruded shell) (2.5 ± 0.05 g) was suspended in distilled water (30 mL) at 25 • C and then centrifuged at 3000× g for 10 min.…”
Section: Techno-functional Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The water absorption index (WAI) was determined according to the method described by Ruiz-Gutiérrez et al [24]. The extruded shell or the control (non-extruded shell) (2.5 ± 0.05 g) was suspended in distilled water (30 mL) at 25 • C and then centrifuged at 3000× g for 10 min.…”
Section: Techno-functional Characterizationmentioning
confidence: 99%
“…The WAI was calculated as the weight of sediment per weight of dry solid shell. The water solubility index (WSI) was the weight of dry solids in the supernatant from the WAI test after decantation and evaporation at 105 • C. The oil absorption index (OAI) was determined by the Ruiz-Gutie Rui et al [24] method with few modifications. The extruded shell and the control (non-extruded shell) (2.5 ± 0.05 g) was suspended in sunflower oil (10 mL) at 25 • C, then stirred for 30 s, and then centrifuged at 3000× g for 10 min.…”
Section: Techno-functional Characterizationmentioning
confidence: 99%
“…Carmona et al [113] used microparticles of orange-yellow cactus pear pulp (Opuntia ficus-indica) as a natural yellow colorant in yogurts. Ruiz-Gutiérrez et al [114] used encapsulated powder from red cactus pear (Opuntia ficus-indica) to pigment extruded cereal, showing in this study that encapsulated powder from red palm fruit can be a natural alternative to synthetic dyes. It can be used to develop functional foods with possible health benefits.…”
Section: Food Dyesmentioning
confidence: 60%
“…Betalain is one of the important pigments that can be used as natural dyes in the food industry (Esquivel, 2016). Several studies have reported the application of betalain in food, that is, sausage (Jeong & Han, 2019; Jin et al., 2014; Sucu & Turp, 2018; van ELBE et al., 1974), noodles (Kim et al., 2015), rice (Alam et al., 2019), sweets (Otálora et al., 2019; Yee & Wah, 2017), cereals (Ruiz‐gutiérrez et al., 2017), sorbet (Omae et al., 2017), bread (Hsu et al., 2019), biscuits (Hidalgo et al., 2018), cookies (Sahni & Shere, 2016), and cupcakes (Alshehry, 2019). In addition, betalain extracts can be applied as a dye sensitizer (García‐Salinas & Ariza, 2019; Kurniawan et al., 2019; Ranjitha et al., 2018) and food packaging (Qin et al., 2020; Yao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%